Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1021/acs.est.5b01215
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Novel Perfluoroalkyl Ether Carboxylic Acids (PFECAs) and Sulfonic Acids (PFESAs) in Natural Waters Using Accurate Mass Time-of-Flight Mass Spectrometry (TOFMS)

Abstract: Recent scientific scrutiny and concerns over exposure, toxicity, and risk have led to international regulatory efforts resulting in the reduction or elimination of certain perfluorinated compounds from various products and waste streams. Some manufacturers have started producing shorter chain per- and polyfluorinated compounds to try to reduce the potential for bioaccumulation in humans and wildlife. Some of these new compounds contain central ether oxygens or other minor modifications of traditional perfluori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
333
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(346 citation statements)
references
References 21 publications
7
333
4
Order By: Relevance
“…Only molecular features with scores above 75% were investigated further through database searching and compound evaluation. The usual workflow involved generation of LC/QqTOF MS spectra and processing, application of advanced QqTOF MS filtering tools, visual inspection of detected peaks, and compound identification with databases and/or compound confirmation with authentic standards, if available commercially . In the following sections, we will refer to Figure and the specific step in the process to which we are referring.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only molecular features with scores above 75% were investigated further through database searching and compound evaluation. The usual workflow involved generation of LC/QqTOF MS spectra and processing, application of advanced QqTOF MS filtering tools, visual inspection of detected peaks, and compound identification with databases and/or compound confirmation with authentic standards, if available commercially . In the following sections, we will refer to Figure and the specific step in the process to which we are referring.…”
Section: Methodsmentioning
confidence: 99%
“…A diagram of the workflow used for identifying known Cl-PFRs and the products of hydrolysis and transformation in the OP study mixture is shown in Figure 1 48,54 In the following sections, we will refer to Figure 1 and the specific step in the process to which we are referring. QqTOF MS (MS/MS or MS 2 ) product ion spectra of qualified precursor ions from the preceding MS-only spectrum.…”
Section: Analytical Workflowmentioning
confidence: 99%
See 1 more Smart Citation
“…Known fluorinated alternatives including short chain PFAAs and perfluoroether carboxylic and sulfonic acids (PFECAs and PFESAs) can adequately replace most C8 and higher homologue uses in many fluoropolymer applications. Although they are less persistent in the biota than the long chain PFASs, they are of concern because they do not break down in the environment and may cause similar toxicological effects as the long chain PFASs (Wang et al, 2013;Scheringer et al, 2014;Blum et al, 2015;Strynar et al, 2015). However, the consequences of the increased production and emission of short chain PFAAs are still largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Research at one fluorochemical production site in Bladen County, North Carolina has documented that Nafionrelated wastes have been released into the nearby Cape Fear River since at least 2012. 81 Moreover, the relatively advanced drinking water treatment plant in the city of Wilmington, North…”
Section: Laboratory Supplies Equipment and Instrumentationmentioning
confidence: 99%